Methylmalonic Acidemia: Can Treatment be Improved? - Michals-Matalon, Kimberlee; Lombardo, Rachel; Bilger, Kimberly; Ross, Nancy; Fuller, Kelly; Freedenberg, Debra; Matalon, Reuben (Journal of Nutritional Therapeutics, 2015)
Methylmalonic acidemia (MMA) is a severe metabolic disorder, particularly with complete deficiency of methylmalonyl-CoA mutase. Dietary restriction has led to overt signs of deficiencies including skin rashes, hair loss, and poor growth. More liberal intake of the restricted amino acids has resulted in better growth and less frequent episodes of illness.